Efectividad de la intervención psicológica en el manejo de la depresión en mujeres con cáncer de mama. - Machado Barba, María José (2023)
ABSTRACT: This study investigated the effectiveness of psychological interventions in managing depression in women with breast cancer through a literature review. A quantitative methodology, synthetic, analytical method, and bibliographic study type were used. Eighty-eight scientific documents, including scientific journal articles and undergraduate and postgraduate theses, were examined and collected from various databases such as Scielo, Elsevier, Taylor and Francis, Dialnet, Scopus, Redalyc, and Google Scholar, published between 2012 and 2022. A non-probabilistic intentional sample of 45 articles was selected based on selection criteria. The CRF-QS method was applied to ensure methodological quality. The results indicated that psychological interventions, particularly cognitive behavioral therapy, group therapy, and family therapy, are highly effective in treating depression in women with breast cancer.